TANGGUNGJAWAB HUKUM USAHA KLINIK KESEHATAN DI KOTA TARAKAN TERHADAP SEGALA RESIKO USAHA - Patrisia Febriani (JURNAL AKTA YUDISIA, 2021)
Abstract This study investigated the legal liability of health clinics in the city of Tarakan for all business risks in terms of the Health Act, the Consumer Protection Act and the Minister of Health’s Regulation on Clinics. As one of many health facilities in Indonesia, clinic is easily accessible by the community. Clinical patients are not only protected by the Health Act but also by the Consumer Protection Act. Clinics as providers of health services are responsible for the actions of health workers to their patients because of the relationship between patients and clinics, which is that the clinic guarantees that every health worker who does his work in the clinic will do his best to heal patients. By basing that the importance of the Informed Concent in medical action, the rights of patients are more respected and protected. The results of the study suggest that clarity of rules and consistency of policies must be increased because they have a huge impact on public trust in the government so that responses to health services will be well coordinated. Doctors / health workers must be more responsible for medical actions that will / have been carried out in the context of fulfilling health services to patients in order to foster an honest and responsible attitude for all health workers who perform health services in the clinic.